2003
DOI: 10.1507/endocrj.50.21
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Corticotropin-Releasing Factor(CRF) Type-1 Receptor Gene Expression by CRF in the Hypothalamus.

Abstract: We reported previously that acute stress and intracerebroventricular (i.c.v.) injection of corticotropin-releasing factor (CRF) increased neuronal activation and CRF type-1 receptor (CRFR-1) mRNA expression in the CRF-producing neurons of the parvocellular paraventricular nucleus (PVN) of the hypothalamus. In this study, to determine whether CRF can act directly on hypothalamic CRF neurons, thereby increasing CRFR-1 expression, microinjection of CRF into PVN neurons in vivo and primary cultures of dispersed ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…These results suggest that the differential up-regulation of CRF R1͞R2 may also depend on their ligand rather than TxA treatment as suggested (16). In this regard, CRF and UcnI have been shown to regulate transcription of CRF-R1 in a positivefeedback loop in both central and peripheral cells (32,33). It is also possible that the message up-regulation for CRF-R2 precedes increase in protein levels.…”
Section: Fig 2 Crf and Ucnii Inhibition Modulate Intestinal Motilitmentioning
confidence: 88%
“…These results suggest that the differential up-regulation of CRF R1͞R2 may also depend on their ligand rather than TxA treatment as suggested (16). In this regard, CRF and UcnI have been shown to regulate transcription of CRF-R1 in a positivefeedback loop in both central and peripheral cells (32,33). It is also possible that the message up-regulation for CRF-R2 precedes increase in protein levels.…”
Section: Fig 2 Crf and Ucnii Inhibition Modulate Intestinal Motilitmentioning
confidence: 88%
“…However, it could be argued that if CRHR-1 plays a major role in the HPA axis activation, the antagonized effects of α-hCRH on each HPA axis that were variably measured in this study should be more potent than those of ASV-30. Previous studies have shown that α-hCRH completely blocked intracerebrovascular CRH induced HPA axis activation or c-fos induction, whereas it partially blocked HPA axis or c-fos responses to various types of stress [22, 23,44,45,46]. It has been postulated that stress activates a number of neurotransmitter systems, including CRH, that in turn increase PVN neuronal activity [47], providing an explanation for the partial antagonizing effects of α-hCRH on the stress-induced HPA axis or c-fos response [45].…”
Section: Discussionmentioning
confidence: 99%
“…Basal expression of CRF 1 mRNA within the PVN is very low. However, in the rat, but not in the mouse, PVN CRF 1 mRNA could be induced via stress exposure or intra-PVN CRF microinfusion (Imaki et al, , 2001Konishi et al, 2003). In the periphery, low levels of CRF 1 mRNA occur in the testis, ovary, retina and adrenal gland.…”
Section: Crf Receptors and Crf Binding Proteinmentioning
confidence: 98%